The influence of deposition technological process parameters on surface properties of multilayer coatings - Zykova, A.; Safonov, V.; Walkowich, J.; Rogowska, R.; Yakovin, S. (Вопросы атомной науки и техники, 2009)
The surface of material plays a basic role in determining of various processes such dyeing penetration, chemical
absorption, biocompatibility and others. At present study the surface parameters investigation for various multilayer
coating types TiN, CrN, (Ti,Cr)N, TiN/TiC₁₀N₉₀, TiN/TiC₂₀N₈₀ and oxide Al₂O₃ films deposited by means Arc-PVD
technology and Reactive Magnetron Sputtering (RMS) methods on the stainless steel (1H18N9) has been made. The
surface thickness, roughness, topography, surface free energy (SFE) was evaluated for next conclusions about surface
properties of multilayer coatings. Поверхні матеріалів відіграють значну роль в проходженні багатьох процесів, таких як фарбування, хiмiчна
абсорбція, бiосумiснiсть та інші. Представлено результати проведених досліджень поверхневих параметрів
багатошарових покриттів TiN, CrN, (Ti,Cr)N, TiN/TiC₁₀N₉₀, TiN/TiC₂₀N₈₀, а також оксидів Al₂O₃, які нанесено за
допомогою методів Arc-PVD та реактивного магнетронного розпилення (РМР) на сталь (1H18N9). Проведена
оцінка товщини, шорткiстi, топографії, поверхневої енергії та інших поверхневих властивостей багатошарових
покриттів. Поверхность материалов играет определяющую роль в прохождении многих процессов, таких как
окрашивание, химическая абсорбция, биосовместимость и другие. Представлены результаты проведенных
исследований поверхностных параметров многослойных покрытий TiN, CrN, (Ti,Cr)N, TiN/TiC₁₀N₉₀,
TiN/TiC₂₀N₈₀, а также оксидных Al₂O₃ пленок, нанесенных методами Arc-PVD и реактивного магнетронного
распыления (РМР) на сталь (1H18N9). Проведена оценка толщины, шероховатости, топографии, поверхностной
энергии и других поверхностных свойств многослойных покрытий.